(untitled) (Research, Society and Development, 2021)
This article aimed to know which technologies improve nursing communication with breastfeeding women. The methodology used was a qualitative research with emphasis on the integrative review of the VHL and SCOPUS databases, in Portuguese, English and Spanish , The included studies were original articles published from 2006 to 2019, with the following descriptors: "breastfeeding"," health communication", "nursing", "women" and "technology". A total of 118 studies were identified, resulting in a total of twenty- six studies analyzed in three categories: (1) empowerment and maternal self-efficacy for breastfeeding; (2) concepts and practices of breastfeeding and(3) health education practices in the promotion of breastfeeding. For the analysis of the results, the classification of Hard, light-hard and light Merhy technologies. Health technologies are still little used by nurses in communication with breastfeeding women even though hard and light-to-hard technologies have been mentioned in part by health professionals. However, it is noticed that in the last five years there has been an increase in the production of studies on the communication of nurses with breastfeeding women. Among them, the use of educational technologies for the empowerment and self-efficacy of women in breastfeeding stands out.